2018
DOI: 10.5604/01.3001.0011.5744
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Structure of Footwear Upper and Lining Materials on Their Electrical Properties

Abstract: Protective footwear for occupational use conducts static electricity through the upper, linings, insole and outsole into the ground. Footwear must be made from appropriate material to reduce the possibility of electrocution and other electricity-related incidents. In this study the influence of footwear materials for the upper and lining components’ structure on their electrical properties was investigated. For investigations leather and various textile laminates were chosen. The thickness of leather coating, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…The results showed lower resistivity values for textiles (3V 2 ) as compared to leather surface (L2). If we compare with literature data which show that the electrical resistivity of leather is lower by more than two orders of magnitude (10 2 Ω) than of textile [12], we can conclude that the treatment with new nanocomposites makes the two materials similar in terms of electric properties.…”
Section: Surface Resistivitymentioning
confidence: 75%
See 1 more Smart Citation
“…The results showed lower resistivity values for textiles (3V 2 ) as compared to leather surface (L2). If we compare with literature data which show that the electrical resistivity of leather is lower by more than two orders of magnitude (10 2 Ω) than of textile [12], we can conclude that the treatment with new nanocomposites makes the two materials similar in terms of electric properties.…”
Section: Surface Resistivitymentioning
confidence: 75%
“…For textile materials synthetic fibres have more static problems compared with natural fibres. Hydrophilic chemical materials and moisture drastically decrease textile and leather resistivity with effect on static electric charges dissipation rate increase and conductive properties development for 95% humidity [12]. There are few studies regarding the functionalization of textile and leather materials by using hybrid TiO 2 / SiO 2 /poly(2,2'-bithiophene) nanocomposites and the influence of treatment technologies on their surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the materials applied inside of footwear, the insole normally retains moisture and heat, which can cause the proliferation of bacteria or fungus [30,31]. Consequently, lining footwear is generally made of textiles, which must have the capacity of draining the moisture and evaporate the water to the upper part of shoes.…”
Section: Footwear Structure and Required Propertiesmentioning
confidence: 99%
“…Other research into electromagnetic shielding investigates the content and placing of a conductive component [9,11,13], geometric structure of a fabric [10,12,14]), humidity of textile [7,12], dependence between electric conductivity and EMSE (electromagnetic shielding effectiveness). Fabric porosity has a very big effect on the shielding factor.…”
Section: Introductionmentioning
confidence: 99%
“…It increases shielding effectiveness of fabrics [8]. Electrical properties of fabrics depend not only on nature and structure but also on moisture accumulation capability [12]. The effect of the diameter and content of a conductive fibre on shielding performance was studied and it was found that greater thickness of a conductive fibre gives better shielding values in higher frequency ranges, but stitch density does not affect shielding performance in the frequency range of 300-3000MHz [13].…”
Section: Introductionmentioning
confidence: 99%